Pengujian Trade Off Theory dan Pecking Order Theory di Jakarta Islamic Index - Wikartika, Ira; Fitriyah, Zumrotul (BISMA (Bisnis dan Manajemen), 2018)
The operations of the company are always faced with the problem of meeting the needs of funds. Company funding is closely related to the selection and combination of internal funding sources and external funding sources. The funding decision of the capital structure determines the company in carrying out its operating activities that affect the company's value. There are two perspectives in determining the funding decision of capital structure, namely trade-off theory and pecking order theory. This study aims to analyze the effect of capital structure funding decision variables according to the perspective of trade-off theory and pecking order theory on funding decision of capital structure. The study population used companies listed in the Jakarta Islamic Index. The sample used is 30 companies during the period of June to November 2016. The result shows that according to trade-off theory, firm size and growth influence to leverage, but tangible fixed assets and profitability have no effect on leverage. While according to pecking order theory perspective, it shows that only variable of growth that influence to leverage. Thus it can be concluded that companies in Jakarta Islamic Index tend to follow trade-off theory perspective.